Proposed framework for combining gamification elements with open learner model in a collaborative e-learning system for programming course / Harizah Jasin ... [et al.] - Jasin, Harizah; Othman, Mahfudzah; Muhd Zain, Nurzaid; Osman, Mohd Nizam (UiTM Cawangan Perlis, 2017)
The main objective of the proposed framework that combines gamification and open learner model is to increase students’ engagement in learning programming via virtual computer environment, thus enabling them to learn cooperatively and helps them to increase awareness of their own performance. The framework proposed the development of an e-Learning system that includes gamification elements such as the users’ level and leaderboard to display users’ achievements and rewards. Meanwhile, in order to increase students’ awareness of their own milestone in the programming course, the framework also included the Open Learnel Model, which shows the students’ milestones via the skills meters. This project also proposed the use of Web 2.0 elements such as chat rooms to allow collaboration and group discussions over the Internet.